Pengaruh model pembelajaran RME (realistic mathematics education) terhadap kemampuan pemecahan masalah pada materi sistem persamaan linear dua variabel di kelas VIII SMP Negeri 2 Pematangsiantar tahun ajaran 2018/2019 - Panggabean, Yosephin Elisabeth (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
The purpose of this research was to known whether there was an effect of Realistic Mathematics Educations (RME) learning model on student’s mathematical problem solving abilities. This research was conducted at State Junior High School 2 Pematangsiantar in the 2018/2019 Academic Year. This research was a quantitative research using a quasi-experimental research type, and the research design was posttest-only control design. The population of this study was all students of class VIII, total 150 students, but the sample was taken by simple random sampling, so that VIII-3 class was chosen as the experimental class and VIII-5 class as the control class with 26 students each classes. The experimental class was implemented with the application of the RME learning model, and the control class was implemented with the application of the conventional learning model. The data collection technique was carried out using that test instruments. From the data analysis’s results, there were significant results from student’s problem solving abilities on the Two Variable Linear Equation System subject matters in class VIII-3 State Junior High School 2 Pematangsiantar. This can be seen from the research hypothesis testing obtained was greater than on a real level.